Individualized Treatment of Hbeag-Negative Chronic Hepatitis B Using Pegylated Interferon-α2A as First-Line and Week-12 HBV Dna/Hbsag Stopping Rule: A Cost-Effectiveness Analysis. Issue 4 (May 2013) - Iannazzo, Sergio; Coco, Barbara; Brunetto, Maurizia R; Rossetti, Francesca; Caputo, Antonietta; Latour, Andrea; Espinos, Belen; Bonino, Ferruccio
Background: Hepatitis B e antigen (HBeAg)-negative chronic hepatitis B (CHB) is the most frequent and difficult-to-treat viral hepatitis worldwide. HBV DNA and hepatitis B surface antigen (HBsAg) serum levels, which help the early identification of non-responders to pegylated interferon (PEG-IFN), prompt more flexible individualized therapeutic strategies exploiting the benefits of both PEG-IFN and nucleoside/nucleotide analogues (NAs). We assessed the cost-effectiveness of week-12 HBV DNA/ HBsAg stopping rule for early interruption and switch to currently most effective NA treatments (entecavir [ETV] or tenofovir disoproxil fumarate [TDF]). Methods: A decision-analytic Markov model was developed in the following health-related states: CHB, compensated cirrhosis (CC) and decompensated cirrhosis, hepatocellular carcinoma, liver transplant, post-liver transplant, death, virological response, relapse and HBsAg clearance. Simulated strategies included: ETV/TDF in CHB; ETV/TDF delayed until CC; first-line PEG-IFN followed by switch to ETV/TDF for either patients meeting the week-12 stopping rule or week-48 null-responders/relapsers; and first-line PEG-IFN followed by switch to ETV/TDF delayed until CC. ETV and TDF were considered alternatively for a total of eight strategies. A lifetime simulation horizon was applied. Results: Early treatment strategies using NAs with or without first-line PEG-IFN provided the highest results (approximately 22 life-years and 15 quality-adjusted life years [QALYs]). Delayed treatments until cirrhosis development resulted in poorer outcomes. The average per-patient lifetime costs ranged from €33, 500 (TDF in CC) to €68, 900 (TDF in CHB). Costs using ETV were 20–50% higher. First-line PEG-IFN strategies ranged from dominant (that is, more effective and less costly) to highly cost-effective, although differences in QALYs were always very narrow. Conclusions: The cost-effectiveness of antiviral therapy of HBeAg-negative CHB could be improved significantly using first-line PEG-IFN followed by a switch to NAs in either patients meeting the week-12 HBV DNA/HBsAg stopping rule or week-48 non-responders/relapsers.